PREGNANCY AND DELIVERY IN WOMEN WITH A HISTORY OF PREECLAMPSIA HYPERHOMOCYSTEINEMIA TREATED WITH BEMIPARIN IN COMBINATION WITH LOW-DOSE ASPIRIN - L. O. Buzyan; G. G. Buzyan; V. F. Dolgushina (IRBIS LLC, 2016)
Preeclampsia is a serious complication of pregnancy and one of the leading causes of maternal mortality. According to modern concepts, the key link in the pathogenesis of preeclampsia is an endothelial dysfunction leadind to persistent prothrombotic hemostasis state. Markers and predictors of preeclampsia considered hypercoagulation, hyperagregation and hyperhomocysteinemia. Women with the history of preterm labor and preeclampsia was treated by antithrombotic correction started on pregravid stage. Pregnancy successfully completed on time delivery without hypertensive complications.